- Analisis Pemanfaatan Limbah B3 Batubara dan Gamping Serbuk sebagai Bahan Tambah Semen terhadap Kekuatan Beton - Ifa Aulia Chusna; Muhammad Wildan Ilyasa; Rahmat Aditya; Tedy Agung Cahyadi; Heru Suharyadi (Retii, 2020)
The planning of 497 steam power plants (PLTU) is one solution in meeting the growing electricity needs (Strategic Plan of Directorate of Electricity, 2015). The development of PLTU in Indonesia, then the waste of Hazardous and Toxic Materials (B3) due to the remaining burning of coal in the form of fly ash and bottom ash is increasing. This B3 waste can pollute the environment if not managed and used properly. This research aims to find out optimal strength if the fly ash, bottom ash, and limestone are used for cement-added materials. The test used is a compression strength test. The molding time of the tube-shaped sample is 28 days with a volume of 196.40 cm3. Sample A as a sample indicator consisting of cement, sand, and gravel with a ratio of 1:2:3. Sample B is made of limestone, sample C is made of bottom ash, and sample D is made of fly ash. The comparison of cement-added materials in each sample was 5%, 15%, and 18% of the cement volume in sample A. The level of use of limestone as a cement added material is 5-15%, while the use of fly ash is optimal at 15-18% content, and the use of bottom ash is only optimal at 5% content.